Le rouleau de cuivre de la grotte 3 de Qumrân (3Q15) : expertise, restauration, epigraphie - Poffet, Jean-Michel.; Puech, Emile.; Brizemeure, Daniel.; Lacoudre, N. (Studies on the Texts of the Desert of Judah, 2006)
This book in two volumes gives the status quaestionis of the Qumran Copper Scroll, fifty years after its discovery. The first part of volume one, amply illustrated with graphics and images, gives the technical expertise of its state of preservation together with the proposals for treatment developed by the laboratory EDF-Valectra for its restoration-conservation. The production of a facsimile by means of galvanoplasty and digitalized images is explained. The second part of volume one gives a largely renewed edition of the engraved Hebrew text with an up-to-date commentary, French and English translations, and indices. The second volume of nearly 400 plates publishes photographs and X-Rays of each segment before and after treatment, as well as the reproduction by means of galvanoplasty and digitalized images.